Assessing the role of REM13, REM34 and REM46 during the transition to the reproductive phase in Arabidopsis thaliana - Silvia Manrique; Francesca Caselli; Luis Matías-Hernández; Robert G. Franks; Lucia Colombo; Veronica Gregis (Plant Molecular Biology, 2023)
REM (reproductive meristem) transcription factors have been proposed as regulators of plant reproductive development mainly based on their specific expression patterns in reproductive structures, but their roles are still largely unknown probably because of their redundancy. We selected three REM genes ( REM13 , REM34 and REM46 ) for functional analysis, based on their genome position and/or co-expression data. Our results suggest that these genes have a role in flowering time regulation and may modulate cell cycle progression. In addition, protein interaction experiments revealed that REM34 and REM46 interact with each other, suggesting that they might work cooperatively to regulate cell division during inflorescence meristem commitment. Previous attempts of using co-expression data as a guide for functional analysis of REMs were limited by the transcriptomic data available at the time. Our results uncover previously unknown functions of three members of the REM family of Arabidopsis thaliana and open the door to more comprehensive studies of the REM family, where the combination of co-expression analysis followed by functional studies might contribute to uncovering the biological roles of these proteins and the relationship among them.